A new halospinel superionic conductor for high-voltage all solid state lithium batteries. Issue 7 (29th June 2020) - Zhou, Laidong; Kwok, Chun Yuen; Shyamsunder, Abhinandan; Zhang, Qiang; Wu, Xiaohan; Nazar, Linda F.
Abstract : A new disordered chlorospinel superionic conductor, Li2 Sc2/3 Cl4, enables high-voltage all solid state batteries up to 4.6 V vs. Li + /Li. Abstract : We report a new Li-superionic chloride, Li2 Sc2/3 Cl4, that crystallizes in a disordered spinel structure, and exhibits an ionic conductivity of 1.5 mS cm −1 with a low activation energy barrier for Li + ion diffusion of 0.34 eV. This material is the first spinel-type superionic halide. Structural elucidation via powder neutron diffraction reveals a significantly disordered Li + -ion distribution over available tetrahedral and octahedral sites within the lattice, forming an infinitely 3D connected Li + ion diffusion pathway comprised of face-sharing octahedra and tetrahedra. Due to the high oxidative stability of Li2 Sc2/3 Cl4, all solid state lithium batteries employing Li2 Sc2/3 Cl4 and high voltage cathodes (LiCoO2, LiNi0.6 Mn0.2 Co0.2 O2 or high-Ni LiNi0.85 Mn0.1 Co0.05 O2 ) – without any coating – exhibit excellent electrochemical performance up to 4.6 V in terms of capacity retention and cycle life.